Two Notions of Frustration of Contract—Impossibility Viz-A-Viz Impracticability: Case Study of Pakistan - Nawaz, Hafiz Muhammad Usman; Dr Muhammad Asim Iqbal,; Syed Mudasser Fida Gardazi, (Journal of Peace, Development and Communication, 2022)
Frustration of contract is one of the modes of discharge of contracts. It is the doctrine which ensures the automatic termination of respective obligations of the parties as well as adjustment of rights and obligations accrued before the frustrating event. There are two famous notions dealing with frustration of contract i.e. physical impossibility and commercial impracticability. Physical impossibility notion is developed and currently is being practice by English Courts. While commercial impracticability notion is recognized and applied by American Courts and Statutes. This article will analyze the both notions in the context of Pakistani legal system to find the application of relevant notion of the doctrine. This article will also discuss different modes of discharge of contracts along with frustration of contract. For that purpose Pakistani law and Case laws of superior courts will be cited and analyzed. This article will be an effort to find the jurisprudence of Pakistan with reference to commercial law generally and with reference to doctrine of frustration of contract especially.